Pollution assessment of selected heavy metals in soil surrounding biomass power plant / Nurul Diana Mat Ail - Mat Ail, Nurul Diana (Faculty of Applied Sciences, 2017)
Problem of heavy metals pollution is becoming more serious with increasing industrialization and disturbance of natural biogeochemical cycles. Heavy metals can give adverse health effect to human and environment. The objectives of this study were to determine the content of the selected heavy metals in topsoil surrounding Biomass Power Plant and to assess the pollution levels based on contamination factor, enrichment factor and geo-accumulation index. Heavy metal that were analyzed included copper (Cu), zinc (Zn) and manganese (Mn). In this study, the soil samples had been air-dried and sieved through 2.12 µm in size and then, the soil samples were analyzed by using Quantexpress (Fast Screening) XRF S8 Tiger. The mean concentrations (mg/kg) for Cu, Zn and Mn were found as 36.4, 17.2 and 66.4 respectively. The analysis of contamination factor showed that the contamination degree of heavy metal in the soil samples is in the class of low contamination degree to moderate contamination degree. Analysis of the Igeo indexes indicates that heavy metal content in soil samples are mostly in the levels of unpolluted. Based on the data of EF, it can be concluded that the soils surrounding Biomass Power Plant is not significantly contaminated with the studied heavy metals.